2022
DOI: 10.1371/journal.pone.0269256
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the mass adoption potential of wearable medical devices

Abstract: Digital technologies empower users to manage their health and reduce the burden on the public health system. The mass adoption of wearable medical devices (WMDs) promotes the ageing population’s confidence besides facilitating users. Thus, the current study aims to empirically evaluate the formation of perceived product value (PPV) with the WMDs’ computability, usefulness, cost, and accuracy, the intention to use WMDs influenced by health consciousness (HCS), health anxiety (HAY), product value, and perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“… 43 Consequently, multivariate data normality examination is accomplished with the online tool of web power ( https://webpower.psychstat.org/wiki/tools/index). 32 The outcome settles that the present data were nonnormal, as Mardia's multivariate coefficient p -values were below .05. 44 …”
Section: Methodssupporting
confidence: 58%
See 3 more Smart Citations
“… 43 Consequently, multivariate data normality examination is accomplished with the online tool of web power ( https://webpower.psychstat.org/wiki/tools/index). 32 The outcome settles that the present data were nonnormal, as Mardia's multivariate coefficient p -values were below .05. 44 …”
Section: Methodssupporting
confidence: 58%
“…Second, HMT was assessed with four items taken from Li et al 25 with the reported Cronbach's Alpha of 0.91. Next, PCM was evaluated using the four items from Yang et al, 32 having Cronbach's alpha for the scale was 0.96. PUF was assessed with four items taken from Kim et al, 5 with Cronbach's alpha of 0.93.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, prior research on health-care wearable technology and its uses tended to concentrate on particular age groups, using the TAM, UTAUT and UTAUT2 perspectives. Interestingly research, to date, has focused primarily on the characteristics that motivate users to embrace a new wearable device (Park, 2020;Yang et al, 2022;Huarng et al, 2022); and another few that focus on its abandonment (Lazar et al, 2015;Shen et al, 2018;Fietkiewicz and Ilhan, 2021;Attig and Franke, 2022), as opposed to those that encourage continued usage. Precisely speaking, there remains a paucity of research regarding user adoption behaviour and the actual use of such technology (Lee and Lee, 2020).…”
Section: Introductionmentioning
confidence: 99%